Safety and efficacy of a novel inactivated trivalent Salmonella enterica vaccine in chickens. Issue 43 (7th October 2020) - Crouch, Colin F.; Nell, Tom; Reijnders, Martine; Donkers, Ton; Pugh, Chris; Patel, Amit; Davis, Phil; van Hulten, Marielle C.W.; de Vries, Stefan P.W.
Highlights: Novel trivalent inactivated Salmonella vaccine was developed and tested in the field. Vaccine was safe with no local or systemic reactions or impact on bird performance. Induction of pronounced serological response which was maintained until at least 56 weeks. Vaccine was efficacious against challenge with homologous and heterologous serovars. Vaccine provides a new tool in comprehensive Salmonella control programmes. Abstract: Food poisoning in humans caused by Salmonella enterica remains a significant global public health concern, with the majority of infections associated with the consumption of contaminated eggs or poultry products. The safety and efficacy of a novel inactivated trivalent Salmonella enterica vaccine containing in addition to Salmonella serovars Enteritidis (O:9, serogroup D) and Typhimurium (O:4, serogroup B) also serovar Infantis (O:7, serogroup C1) formulated with an aluminium hydroxide-gel adjuvant was evaluated under field conditions. A total of 10, 229 broiler breeder pullets, housed under commercial conditions, were vaccinated at 10 and 17 weeks of age by the intramuscular route in the breast muscle. The vaccine was safe with no local or systemic reactions or adverse effects on bird performance related to the vaccine detected. Vaccination resulted in notable increases in serovar specific antibodies that were maintained until at least 56 weeks of age. Vaccinated birds subjected to homologous challenges around onset of lay showed significantly reduced faecal shedding and organ invasion. Following heterologous challenge with S. Hadar (O:8, serogroup C2) faecal shedding was significantly reduced. These results demonstrate that this novel vaccine could play a significant role in a comprehensive Salmonella control programme intended to reduce both the incidence of food poisoning in humans and the use of antibiotics during poultry production.